Third molar: position, caries, periodontal disease and quality of life (Research, Society and Development, 2022)
Third molar teeth(3M) position can lead to periodontal disease(PD), caries and may also a significant impact on the oral health related quality of life (QoL). The aim of this study was to verify possible associations between QoL, PD, caries lesions and the position of the lower 3M. An observational cross-sectional study was performed in 116 patients (228 teeth), with the approval of ethics committee (280084) from University of São Paulo Dental School and registered on Clinicaltrials.gov (NCT04024644). Caries, PD and QoL were the evaluated outcomes. Caries were assessed by visual tactile examination and PD through probing sites around 3M. Both diseases were complementary diagnosed with radiographic’s exams. The assessment of QoL was carried out using the Oral Health impact Profile questionnaire(OHIP-14), applied as an interview. The evaluation of the 3M’s position was performed according to the classification of Pell; Gregory, 1942/Gregory and Winter. Data were analyzed according to STATA 13.0 with 95% of level of significance The higher degree of eruption and angulation of the 3M increased the incidence of caries and PD in these teeth. Age was also a risk factor that increased the occurrence of these oral diseases which negatively influenced the QoL. Patients with caries have impact on domains 1 and 7 and those with PD had impact on domain 2 and 7. Pathologies on the 3M region had an impact on domain 7. 3M’s position influences the incidence of caries and PD in the lower 3M, with consequent negative impacts on the QoL.